Efeitos do laser terapêutico e do ultrassom pulsado de baixa intensidade na expressão de genes relacionados à diferenciação celular durante o processo de reparo ósseo - Pípi, Elaine Fávaro (2010)
Fractures of delayed consolidation and fractures with non-union are commonly found in medical practice and are associated with high morbidity and mortality. Within this context, biochemical and biophysical resource have been studied in an attempt enhance bone healing. Among these may be highlighted the use of low level laser therapy (LLLT) and low intensity pulsed ultrasound (LIPUS). Several studies suggest that both resources are able to stimulate osteogenesis at the fracture site, promoting a greater deposition of bone mass and accelerating the process of bone healing. However, despite a series of biomechanical and radiographic evidence of the effectiveness of LLLT and LIPUS in the bone repair, the celullar and molecular mechanisms that regulate and modulate the acceleration of the fracture consolidation are unknown. So the main purpouse of the present work was to measure the effects of LLLT and LIPUS in the expression of osteogenic genes during the process of bone healing and to extend prior histological description after a bone created defect on of the tibiae in rats. For the study 90 male Wistar rats were underwent surgery for creation of bone defects in both tibias. The animals were randomly distributed into three groups: control group ( bone defect without treatment), bone defect treated with LLLT and bone defect treated with LIPUS. Each group were divided into 3 different subgroups (n=10) that received 3,6 and 12 sessions of treatment, and after 24 hours of each session was the euthanasia of animals on days 7, 13 and 25 days after surgery, respectively at each treatment session. Both tibias were removed and subjected to protocols for histological analysis and gene expression analysis by real time real time PCR. Was observed in the qualitative histological analysis that the animals treated with LLLT showed a greater area of new bone formation within 7, 13, 25 days. Furthermore, morphometric analysis demonstrated increased bone tissue only in animals treated with LLLT in 13 and 25 days. It was verified an increase in mRNA levels of BMP4 in the 13 days of the LLLT group and the ALP, Runx2 and BMP4 in 25 days after the application of LLLT and LIPUS, and the mRNA of ALP was more expressed in the LLLT group . We conclude that LLLT stimulates bone formation by increasing the mRNA expression of BMP4 in the 13 days and the ALP in the 25 days.